Specification of strong position by the toll blasting of hydration material messaging on the peal changing-state consciousness system of skin - Jeonglae Kim; Hyeju Kim (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Peal changing-state technology is consisted the reverberation status for seamless-polka-dot pattern of thebrighten consciousness rate (TCR) and gap consciousness rate (DCR) on the peal consciousness imagery of skin. The consciousness rate condition by the peal consciousness imagery is consisted with the toll reverberation system of skin. As to recover a seamlesspolka-dot pattern of the strong changing-state, we are consisted of the peal value with peal layer situation by the toll-down take shape. The conceptof consciousness rate is heck out the reference of brighten rate and gap rate for changing-state signal by the peal reverberation imagery. Moreover to represent a strong changing-stateof the BCR-GCR of the average interms ofthe pealreverberation imagery, and peal situation reverberation that is found the a peal value of the far changing-state of the Pe-ci-FAηAVG with 16.97±9.24 units, that was the a peal value of the convenient changing-state of the Pe-ci-CO-ηAVG with 8.66±3.08 units, that was the a peal value of the flank changing-state of the Pe-ci-FL-ηAVG with 2.80±0.74 units, that was the a peal value of the vicinage changing-state of the Pe-ci-VI-ηAVG with 0.55±0.20 units. The toll reverberation will be to conjecture at the ability of the peal-reverberation imagery for the restrain degree consciousness rate on the BCR-GCR that is to be explainedthe strong brighten and gap imagery by the consciousness rate system. We will be conjecture of imageryby thegap signal and to investigate a peal data of toll reverberation rate by the toll consciousness system.